POTENSI SAMPAH SEBAGAI BAHAN BAKU PUPUK ORGANIK - Hermawan Budiyanto; Sriyanto Sriyanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2011)
Population growth needs to be matched increase in agricultural production, to avoid food crisis. Increased production pursued through intensification, with inorganic fertilizer. In the